The Effect of Low Temperature on some Physiological and Biochemical Trait of some Semi-orange Genotype in the North Iran - saleh Mohammadi; Hamireza khazaie; Ahmad Nezami; Yahya Tajvar (Majallah-i ̒Ulum-i Bāghbānī, 2018)
Introduction: Among citrus producing provinces in the country, Mazandaran province ranks first with 1.88 million tons yields. Orange is one of the horticulture crop which is sensitive to low temperature stress. Low temperature stress is one of the abiotic stresses that its negative effects is the disruption of the electron transfer process through the thylacoid membrane. Actived oxygen radicals can be reacted with methyl unsaturated fatty acid groups and produce active fatty acid radicals. Very reactive formed radicals are capable of initiating lipid peroxidation chain reactions, which leads to the accumulation of free oxygen radicals that can lead to degradation of plant chlorophylls and membrane peroxidation and disruption of photosynthesis, accumulation of ROS, damage to cell membranes, destruction of plant pigments and nucleic acids. Plants can resist against low temperature stress by water saving and utilization of antioxidant system. The amount of free proline in many plants increases in response to environmental stresses such as cold and drought stress, and this physiological response can affect the resistance of the herbal substance under stress. Due to the diversity of citrus native genotypes in the country, the aim of this study was to determine the tolerance of native genotypes against low temperature stress in north of the country. Materials and Methods: This experiment was conducted during the years 2015_2016 at the Citrus and Semi-Traditional Fruit Research Center in Ramsar with the aim of determining the low temperature tolerance of six native pseudo orange genotypes at 4 temperature levels (3, 0,- 3,- 6), compared to The test was carried out by Unsho and Sensitive Persian Lime (low temperature stress). Therefore, in this study, the vulnerability to low-stress conditions in controlled environmental conditions was compared with that of temperature treatments (3, 0, _3 and -6 degrees Celsius) in six genotypes of native pseudo-orange (number 1-6) sensitive cultivar (Persian lime) and resistant cultivars (Unsho) were investigated. This experiment was conducted as a factorial in a completely randomized design. The results of analysis of variance showed that temperature, genotype and interaction of these two treatments were significant in lipid peroxidation, proline, antioxidant capacity, ion leakage, hydroxylation, chlorophyll a and chlorophyll content. The temperature of the device began to decrease at a temperature of 6 ° C. The temperature of the device was 1 ° C / hour, after which the samples were kept at the specified temperatures for 3 hours and at the end of this period (3 Clock) sampling was performed to measure the traits. Accordingly, the leaf aquaculture was calculated by calculating the leaf area using a leaf surface gauge device. Ionic leakage measurements were also investigated using the method of the conversation and Meg Donald method. The presence of genotypes under cold stress led to an increase in malondialdehyde. In these conditions, due to increased oxidative activity, the accumulation of antioxidant compounds such as superoxide dismutase, glutathione peroxidase and catalase increased. The data obtained from this research were based on factorial experiment in a completely randomized design with three replications of analysis of variance and then averages were compared by Tukey test at 5% level using SAS software. Results: Orange is a low temperature stress sensitive horticultural plant. Therefore, in this study, the vulnerability to low temperature stress in controlled environment (3, 0, 3- and -6 degrees Celsius) in six native poderotal genotypes (No.1-6) sensitive cultivars (Persian Liam) and resistant cultivars (Unsho) were studied. This experiment was conducted as a factorial in a completely randomized design. The results of analysis of variance showed that temperature, genotype and interaction of these two treatments were significant in lipid peroxidation, proline, antioxidant capacity, ion leakage, hydroxylation, chlorophyll a and chlorophyll content. Meanwhile, soluble carbohydrate was only affected by the simple factor of genotype. No effects on chlorophyll b and carotenoid pigments were significant. The highest incidences (99.33%), ion leakage (91.63%) and lipid peroxidation reaction (with a mean of 3.33 μg / kg of fresh leaf weight) were recorded in sensitive lambspeed control at 6 °C. In contrast, the highest amount of proline (32.01 mg / g leaf weight) and antioxidant capacity (73.36%) was recorded in the control group at 3 °C. Among the native pseudo-orange genotypes, in this study, different reactions were also observed under low-temperature stress conditions. Accordingly, after the control of the bird, the native pseudo-orange genotype number one was better than the one under temperature decrease. However, in most of the studied orange genotypes, in most of the destructive traits, the native pseudo-orange genotype number 6 was in the same statistical position or close to the sensitive Peninsula. The presence of genotypes under cold stress led to an increase in malondialdehyde. In these conditions, due to increased oxidative activity, the accumulation of antioxidant compounds such as superoxide dismutase, glutathione peroxidase and catalase increased.